Exosomal let‐7f‐5p derived from mineralized osteoblasts promotes the angiogenesis of endothelial cells via the DUSP1/Erk1/2 signaling pathway. (8th November 2022) - He, Yiqun; Li, Hailong; Yu, Zuochong; Li, Linli; Chen, Xujun; Yang, Aolei; Lyu, Feizhou; Dong, Youhai
Abstract: Blood vessel formation is the prerequisite for the survival and growth of tissue‐engineered bone. Mineralized osteoblasts (MOBs) have been shown to regulate angiogenesis through the secretion of exosomes containing various pro‐angiogenic factors. However, whether the mineralized osteoblast‐derived exosomes (MOB‐Exos) containing let‐7f‐5p can regulate the angiogenesis of endothelial cells (ECs) is still unknown. In this study, the angiogenic capabilities of ECs respectively treated with MOB‐Exos, let‐7f‐5p mimicked MOB‐Exos (miR mimic group), and let‐7f‐5p inhibited MOB‐Exos (miR inhibitor group) were compared through in vitro and in vivo studies. Moreover, the potential mechanism of MOB‐Exo let‐7f‐5p regulating angiogenesis was explored by verifying the role of the Erk1/2 signaling pathway and target gene DUSP1. The results showed that MOB‐Exos could significantly promote the angiogenesis of ECs, which could be enhanced by mimicked exosomal let‐7f‐5p and attenuated by inhibited exosomal let‐7f‐5p. Let‐7f‐5p could suppress the luciferase activity of wide‐type DUSP1, and the mutation of DUSP1 could abrogate the repressive ability of let‐7f‐5p. Furthermore, the expression of DUSP1 exhibited a reversed trend to that of pErk1/2. The expression of pErk1/2 was significantly higher in the miR mimic group and lower in the miR inhibitor group than that in the MOB‐Exos group, while inhibition of pErk1/2 could partly impair the angiogenic capabilities of ECs. In conclusion, we concluded that exosomal let‐7f‐5p derived from MOBs could promote the angiogenesis of ECs via activating the DUSP1/Erk1/2 signaling pathway, which might be a promising target for promoting the angiogenesis of tissue‐engineered bone.